Is Ethnicity an Important Determinant of High Blood Pressure in Nepalese Population? A community-Based Cross- Sectional Study in Duwakot, Nepal - Vaidya, A (Kathmandu University Medical Journal, 2012)
Background Hypertension is a rising public health problem in Nepal. Most of the upsurge is attributed to the behavioural and lifestyle transitions. However, the hereditary component such as ethnicity, which may also be an important determinant, has not been studied. Objective This study aims to investigate if ethnicity is a key determinant of having a high blood pressure in the Nepalese population. Methods A population-based cross sectional study was conducted in the Duwakot village of Bhaktapur District, Nepal. Systematic random sampling of the adults was done in all the nine wards. A total of 641 adults of both sexes, of age 35 years or more were included in the analysis. Results Most of the life-style related risk factors were comparable in the broad two ethnic groups- Tibeto-Burmans and Indo-Aryans. The prevalence of hypertension was 25.3% in the Tibeto-Burmans compared to the 14.0% in the Indo-Aryans. Crude odds ratio (95% CI) of being hypertensive for the Tibeto-Burmans compared to the Indo-Aryans was 2.07 (1.36-3.15) (p=0.01). After adjusting for the different factors the adjusted odds ratio (95% CI) for the same was found to be 1.78 (1.12-2.81) (p=0.014). Conclusion There is an ethnic variation in the blood pressure distribution in the Nepalese population, which might be acting independent of the different life-style factors. More elaborate studies, including longitudinal and migration studies, and probably genetic analyses, can provide a more definite answer. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 20-23 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6908